Cardiac Resynchronization Therapy Plus Coupled Pacing Improves Acutely Myocardial Function in Heart Failure Patients. Issue 7 (27th January 2014) - BRÉMONT, CAMILLE; LIM, PASCAL; ELBAZ, NATHALIE; DAMY, THIBAUD; GUÉRET, PASCAL; DUBOIS‐RANDÉ, JEAN‐LUC; WALLICK, DON W.; LELLOUCHE, NICOLAS
<x xml:space="preserve">Abstract</x> Background Coupled pacing (CP), which consists of an additional beat delivered after ventricular refractory period, has been proposed to reduce ventricular rate and increase ventricular contractility. We hypothesized that CP may be added to cardiac resynchronization therapy (CRT) to improve CRT effect in heart failure (HF) patients. Methods The study included 20 consecutive HF patients in sinus rhythm referred for CRT‐defibrillator (CRT‐D) implantation (baseline left ventricular ejection fraction [LVEF] 27 ± 6%, baseline QRS duration 149 ± 33 ms, age = 63 ± 11 years). CP associated with CRT (CRT + CP) was delivered during CRT‐D implantation from the right and left ventricular leads simultaneously. Echocardiography data were collected at baseline, during CRT and CRT + CP to assess changes in LVEF, cardiac output (CO), longitudinal global strain assessed by speckle tracking, and LV dyssynchrony (opposing wall delay using tissue Doppler imaging). Results Compared to the conventional CRT, heart rate (HR) markedly decreased during CRT + CP (79 ± 20 beats/min vs 51 ± 8 beats/min, P < 0.0001) and was associated with a significant increase in LVEF (30 ± 8% vs 35 ± 8%, P = 0.0002) and peak of longitudinal global strain (–6 ± 2% vs –8 ± 2%, P < 0.0001). Importantly, during CRT + CP, CO increased (3.8 ± 1.0 L/min vs 4.4 ± 1.4 L/min, P = 0.004) and cardiac synchronicity remained unchanged (38 ± 24 ms for CRT alone vs 27 ± 18 ms for CRT + CP, P = 0.1). Conclusion In sinus rhythm HF patients, acute CP application in addition to CRT decreases HR and contributes to myocardial contractility and CO improvement without deleterious impact on ventricular synchronicity.